Effectiveness of seated combined extension-compression and transverse load traction in increasing cervical lordosis - Pooke, Tamara Gien (2017)
Changes in sagittal spinal alignment are gaining more importance in terms of treatment outcomes, as abnormal spinal postures result in altered biomechanics that ultimately result in dysfunctions and pathologies. As such, new methods for improving sagittal alignment are being sought. The goal of this study was to assess the effectiveness of seated combined extension-compression and transverse load traction (ECTL) traction as one such method, to determine if it is effective in increasing a reduced lordosis of less than 30 degrees in a Malaysian population between the ages of 18 and 60 years. Secondary objectives such as changes in clinical outcomes of pain and disability were also assessed, along with degenerative findings and possible changes in disc height. These changes were also assessed for any possible differences between gender, age and race. The theory of how this type of ECTL traction can improve a reduced cervical lordosis is based on creep, as well as on the three-point bending mechanism. By creating tension in the anterior cervical structures, this should result in permanent elongation of these structures, and thereby allow improvement of a reduced cervical curve. This was a single center, randomized, blinded controlled clinical trial with parallel groups, used to test the superiority of the seated combined ECTL traction together with physiotherapy exercises as compared with the same physiotherapy exercises used as a control. Fifty randomly allocated subjects who completed the forty treatments over the fourteen weeks were analyzed using non-parametric tests for changes in cervical lordosis and clinical outcomes. The treatment group was subjected to seated combined ECTL traction in combination with physiotherapy exercises, and the control group was subjected to the same physiotherapy exercises only. There were no significant changes seen, with both of the intervention groups showing a non-significant decrease in cervical lordosis rather than the hypothesized increase. Clinical outcomes of pain and disability were assessed and were the only outcomes in this study to show significant improvement, however, there were no significant differences seen between the two groups in terms of any of the other measured outcomes. It was determined that neither intervention used in this study was effective in increasing a reduced cervical lordosis. There were however significant changes seen in the clinical outcomes of pain and disability, in contrast to the curve findings, which further adds to the evidence that suggests that cervical alignment and pain and disability are not related. The findings of a greater overall increase in posterior disc height compared with anterior disc height changes, and greater height changes occurring in the control group, are also in contrast to the proposed underlying theoretical framework for this type of ECTL traction.